(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Due to ongoing pandemic, majority of the academic teaching is executed on online platforms, leadingto extended screen time. Anecdotal evidence suggests long-term ophthalmic impact of extended screentime. Present study was carried out to document eye related problems amongst adult university/collegestudents undertaking online classes to document the effects of online teaching. An online survey method wasundertaken in the month of July, 2020 amongst university/ college students of Gujarat using google form.All possible social media platforms were used to collect the data from students of Gujarat. Epi Info andSPSS were used and both descriptive and inferential analysis was performed. A total of 620 students fromthe various streams participated in the study where around 56.5% were female respondents. The majorityof students (88% of participants) had noticed eye problems out of that 39.1% of participants felt that onlineteaching as a reason. Headache (54.0%) was the most common problem experienced by the participantsfollowed by Pain in eyes (34%) and Watering (26.3%). To conclude online teaching has led to increasedeye strain and other eye-related problems in university/college going students and risk factors for severityincluded sessions attended per day, the distance at device kept, and the enjoyment level. In spite of the highincidence of ophthalmic issues, none of the respondents contacted any ophthalmologist for the same.